DAYA TARIK WISATA PADA DESTINASI WISATA ZIARAH MAKAM SYEKH ABDURRAHMAN SIDDIQ DI HIDAYAT KABUPATEN INDRAGIRI HILIR - Fatimah, Siti; Ibrahim, Mariaty (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This study aims to identify and understand the various tourist attractions found at the religious tourism destination of Makam Syekh Abdurrahman Siddiq, located in Hidayat, Indragiri Hilir Regency, Riau. The research uses a descriptive qualitative approach with data collected through interviews, observations, and documentation. The findings indicate that the main attraction of this destination lies in the religious and historical values attached to Syekh Abdurrahman Siddiq as a prominent Islamic scholar and Mufti of the Indragiri Kingdom. Pilgrimage activities, the